2016
DOI: 10.1021/acs.jmedchem.5b01474
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Acidic Protein–Basic Protein 1 (PA–PB1) Protein–Protein Interaction as a Target for Next-Generation Anti-influenza Therapeutics

Abstract: The limited therapeutic options against the influenza virus (flu) and increasing challenges in drug resistance make the search for next-generation agents imperative. In this context, heterotrimeric viral PA/PB1/PB2 RNA-dependent RNA polymerase is an attractive target for a challenging but strategic protein-protein interaction (PPI) inhibition approach. Since 2012, the inhibition of the polymerase PA-PB1 subunit interface has become an active field of research following the publication of PA-PB1 crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 103 publications
(227 reference statements)
1
56
0
Order By: Relevance
“…Yet, for all the PA C ‐PB1 N interaction inhibitors reported thus far, mechanistic studies using cocrystallization or resistance selection remain to be performed to verify their antiviral mode of action and precise binding mode. This could also aid to design PA C ‐PB1 N assembly inhibitors, which establish hydrophilic besides hydrophobic interactions, thereby leading to better solubility and potentially higher antiviral potency than the current lead compounds …”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…Yet, for all the PA C ‐PB1 N interaction inhibitors reported thus far, mechanistic studies using cocrystallization or resistance selection remain to be performed to verify their antiviral mode of action and precise binding mode. This could also aid to design PA C ‐PB1 N assembly inhibitors, which establish hydrophilic besides hydrophobic interactions, thereby leading to better solubility and potentially higher antiviral potency than the current lead compounds …”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 99%
“…This could also aid to design PA C -PB1 N assembly inhibitors, which establish hydrophilic besides hydrophobic interactions, thereby leading to better solubility and potentially higher antiviral potency than the current lead compounds. 232 Another protein-protein interface that was validated with peptide inhibitors 233,234 but is as yet unexplored with small molecules, is the interaction domain between PB1 C (residues 678-757; Fig. 8C, in light green) and PB2 N (residues 1-37; in dark green).…”
Section: Protein-protein Interaction Inhibitors Of the Influenza Pmentioning
confidence: 99%
“…Previous studies have shown that PB1 serves as a core subunit to incorporate PA and PB2 into the polymerase complex by directly interacting with PA and PB2 (Hemerka et al, 2009). Recently studies also reveal that PB1 interacted with PA was an attractive target for drug treatment (Massari et al, 2016; Swale et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Another appealing strategy to inhibit RdRp function is to interfere with its proper assembly using PPI inhibitors. To this end, small molecule compounds targeting the PA-Cter and PB1-Nter interplay have been actively pursued since 2012 (Massari et al, 2016;Muratore et al, 2012;Yuan et al, 2016d). Intriguingly, anti-influenza agents targeting the PB1-Cter and PB2-Nter interface have never been reported yet.…”
Section: Introductionmentioning
confidence: 99%